2018
DOI: 10.1155/2018/6872753
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Genotoxicity and Subchronic Oral Toxicity of Synthetic Curcumin

Abstract: A battery of toxicological studies was conducted in accordance with international guidelines to investigate the genotoxicity and repeated-dose oral toxicity in rats of synthetic curcumin (VEAMIN 99, >99% purity). There was no evidence of mutagenicity in a bacterial reverse mutation test, whereas an in vitro mammalian chromosomal aberration test was positive for induction of chromosomal aberrations which is in line with results reported for natural curcumin. There was no evidence of genotoxicity in an in vivo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Furthermore, curcumin at the single dose of 5000 mg/kg body weight that was given orally to Swiss albino mice did not show any toxic effects during 14 days with no pathological effects observed and no deaths occurred [41]. In addition, 500 mg/kg BW, 1000 mg/kg BW, and 2000 mg/kg BW of oral curcumin showed no significant genotoxicity in mice [42]. Hepatotoxicity, decreases in weight, and reduction of hemocytes were the main side effects observed in animals as summarized by Soleimani et al [43].…”
Section: Safety and Toxicity Of Curcumin Administrationmentioning
confidence: 85%
“…Furthermore, curcumin at the single dose of 5000 mg/kg body weight that was given orally to Swiss albino mice did not show any toxic effects during 14 days with no pathological effects observed and no deaths occurred [41]. In addition, 500 mg/kg BW, 1000 mg/kg BW, and 2000 mg/kg BW of oral curcumin showed no significant genotoxicity in mice [42]. Hepatotoxicity, decreases in weight, and reduction of hemocytes were the main side effects observed in animals as summarized by Soleimani et al [43].…”
Section: Safety and Toxicity Of Curcumin Administrationmentioning
confidence: 85%
“…There are a large number of toxicological studies of curcumin performed in various experimental models and using different forms of curcumin (extracts, particles, suspensions, etc.). Although most in vivo studies do not report toxic effects (110), some in vitro studies showed mutagenic effects due to damage to mitochondrial and nuclear DNA using high doses (111). Although curcumin exhibits excellent anti-inflammatory properties, and researchers have published that there is little toxicity in vivo, their low stability, poor absorption, and rapid metabolism have promoted the development of synthetic analogs to be implemented in the clinic (112,113).…”
Section: Curcuminmentioning
confidence: 99%
“…Further, it has been shown that Curcumin may be toxic to eukaryotic cells at the concentration above 10 µg/mL. 30 In the present study, we used Nano-Curcumin that has more solubility than exact Curcumin in water. However, Nano-Curcumin was dissolved in a maximum at a concentration of 25 µg/ mL in the presence of 10% DMSO.…”
Section: Discussionmentioning
confidence: 99%